Legibility of Safaieh neighborhood in the city of Yazd, Iran - Sadrabadi, Masomeh Roustaei (2014)
Today, cities are developed to simplify human activities and well-being. Facilitating human activities is depending on the structures and characteristics of the physical elements of cities. In the context of Iranian cities, it is observed that in the majority of new urban areas such as Safaieh neighborhood, most of residents are facing challenges to find their way around. This is due to the fact that the physical elements are unable to cooperate with psychological aspects to enhance legibility of the environment. In this respect, different scholars and researchers in environmental design and environmental psychology fields argued that there is a strong relationship between arrangements of the physical elements and legibility of the city. In this regard, Lynch’s notable work which described the concept of legibility based on physical elements which refers to the ease with which type characters can be read has been fundamental basis for the analysis in the urban design and planning. In order to enhance legibility of Safaieh neighborhood, this study aims to identify physical elements and psychological aspects of the urban environment to enrich people’s wayfinding and orientation in a new area (Safaieh neighborhood) of Yazd City-Iran. Based on mental mapping technique and interviews, Lynch identified five physical elements that influence how people structure a city. The elements are landmarks, paths, nodes, edges and districts. The study extended the investigation by examining the effects of these physical elements on the psychological aspects which are human wayfinding and orientation. It is argued that one’s wayfinding and orientation are dependent on the physical elements in the city. The study adopted both qualitative and quantitative methods to identify physical elements in the new area of Yazd city in Safaieh neighborhood and to examine the effect of physical elements on people’s wayfinding and orientation in Safaieh neighborhood. Field observation was conducted to understand the structure of the city and elements defining the city while structured questionnaire surveys were used to gauge the respondents’ opinions and knowledge about the physical elements that affect wayfinding and orientation. The questionnaire survey was conducted with 102 participants of Safaieh neighborhood residents to identify the legible elements within the city. Then, the semi-structured interviews were conducted with 100 respondents using a set of open-ended questions together with sketch mapping to capture their mental images of the physical elements and to gather information on issues related to the city and characteristics associated with wayfinding and orientation. The study found that from the perspectives of the respondents, the physical elements are not legible enough to provide clear image for residents to have a good perception of environmental information and thereby reduces their wayfinding and orientation ability. The findings of the study assist urban planners to understand the effect of physical elements on wayfinding and orientation and to plan for a strategy to enhance the legibility of urban setting. Therefore the outcome could be used to improve wayfinding and orientation ability of residents in different neighborhoods in Iranian cities.